2021
DOI: 10.12928/fokus.v11i1.3734
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kredibilitas Influencer Pada Efektivitas Iklan Media Sosial Instagram Dalam Membentuk Minat Beli Konsumen (Studi Pada Pengikut Instagram Ayudia Bing Slamet)

Abstract: This study aims to analyze the influence of influencers' credibility on the effectiveness of Instagram social media advertising in shaping consumer buying interest (Study on Instagram followers Ayudia Bing Slamet). The subjects in this study were students using social media Instagram who were in the Special Region of Yogyakarta. This research was conducted with a sample size of 200 respondents who were determined by sampling technique using non probability sampling technique with purposive sampling method and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…Trustworthiness: Past research has indicated that the trust customers place in social media influencers, along with their content and posts, is significantly impacted by their level of trustworthiness (Lou & Yuan, 2018). Jelita & Rimiyati (2021) discovered that confidence in influencers is crucial in influencing consumer perceptions of advertising on social media. As a result, it has been determined that the credibility of social media influencers greatly influences followers' chances of making a purchase.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Trustworthiness: Past research has indicated that the trust customers place in social media influencers, along with their content and posts, is significantly impacted by their level of trustworthiness (Lou & Yuan, 2018). Jelita & Rimiyati (2021) discovered that confidence in influencers is crucial in influencing consumer perceptions of advertising on social media. As a result, it has been determined that the credibility of social media influencers greatly influences followers' chances of making a purchase.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Hal tersebut menyebabkan peningkatan pengguna internet di Indonesia sangat pesat sehingga persaingan usaha yang berbasis onlinepun semakin ketat. Media sosial merupakan salah satu media online yang sangat penting bagi promosi oleh banyak perusahaan dan salah satu cara terbaik untuk menjangkau pelanggan secara luas (Jelita & Rimiyati, 2021). Salah satu cara yang digunakan oleh Scarlett Whitening untuk memperkenalkan produknya adalah dengan menggunakan selebriti sebagai bintang iklan dalam memasarkan produknya.…”
Section: Pengujian Hipotesisunclassified